How Is The National Banking Marketing Strategy Based On Technology - syafril, syafril; Effiyaldi, Effiyaldi; Selvanus, Selvanus; Wahyudi, Wahyudi (Lembaga Pengembangan Kinerja Dosen, 2024)
This research explains a phenomenon of how national banking marketing strategies are technology-based. This research uses an exploratory qualitative method with a literature study approach which tries to produce information and knowledge in a field that was previously under-researched. The research results show that national banking marketing strategies developed in accordance with advances in technology during that time. Current technological developments have brought about fundamental changes in national banking, such as the presence of branchless banking and digital banking based on internet technology. The next development will change banking marketing strategies starting the marketing 5.0 era based on humanity and technology. It is hoped that the results of this research will be useful for the world of banking and science in the future.